ANALISIS PROSES BERPIKIR KREATIF MATEMATIS SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA PERSAMAAN DAN PERTIDAKSAMAAN LINEAR SATU VARIABEL DITINJAU DARI TIPE KEPRIBADIAN EXTROVERT DAN INTROVERT - Adinda Mayla Rizqiyati; Fitria Zana Kumala (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2023)
The background of this research is the low mathematical creative thinking process of class VII B SMP Muhammadiyah Tonjong Brebes Regency in solving mathematical problems of one-variable linear equations and inequalities. One of the influencing factors is the personality type possessed by students, both extrovert and introvert personality types. This study aims to determine students' mathematical creative thinking processes in solving mathematical problems of one-variable linear equations and inequalities in terms of the extrovert and introvert personality types of students at SMP Muhammadiyah Tonjong, Brebes Regency. This type of research is Mix Method Research (MMR). The subjects of this study were students in class VII B at SMP Muhammadiyah Tonjong, Brebes Regency, for the 2022/2023 academic year, with a total of 6 subjects. The instruments in this study were personality questionnaires to determine students' personality types, both extroverted and introverted, and written test instruments to assess students' mathematical creative thinking processes. Based on the analysis that has been done, the extrovert personality type students, with a total of 17 students, are divided from the creative group of 6 students who meet all four indicators (fluency, flexibility, originality, and elaboration), the moderately creative group of 7 students fulfills three indicators (fluency, flexibility, and elaboration ), and four students in the less creative group fulfilled two indicators (flexibility and originality). While students with introverted personality types, a total of 14 students were divided into creative groups of 2 students fulfilling all four indicators (fluency, flexibility, originality, and elaboration), moderately creative groups of 9 students fulfilling three indicators (fluency, originality, and elaboration), and three students in the group less creative does not meet one of the four indicators.